Measurement of nicotine withdrawal symptoms: linguistic validation of the Wisconsin Smoking Withdrawal Scale (WSWS) in Malay - Awaisu, Ahmed; Samsudin, Sulastri; Amir, Nur Afni; Omar, Che Gayah; Hashim, Mohd Ikhwan; Nik Mohamed, Mohamad Haniki; Shafie, Asrul Akmal; Ahmad Hassali, Mohamed Azmi (BioMed Central, 2010)
Background: The purpose of the linguistic validation of the Wisconsin Smoking Withdrawal Scale (WSWS) was to produce a translated version in Malay language which was "conceptually equivalent" to the original U.S. English version for use in clinical practice and research. Methods: A seven-member translation committee conducted the translation process using the following methodology: production of two independent forward translations; comparison and reconciliation of the translations; backward translation of the first reconciled version; comparison of the original WSWS and the backward version leading to the production of the second reconciled version; pilot testing and review of the translation, and finalization. Results: Linguistic and conceptual issues arose during the process of translating the instrument, particularly pertaining to the title, instructions, and some of the items of the scale. In addition, the researchers had to find culturally acceptable equivalents for some terms and idiomatic phrases. Notable among these include expressions such as "irritability", "feeling upbeat", and "nibbling on snacks", which had to be replaced by culturally acceptable expressions. During cognitive debriefing and clinician's review processes, the Malay translated version of WSWS was found to be easily comprehensible, clear, and appropriate for the smoking withdrawal symptoms intended to be measured. Conclusions: We applied a rigorous translation method to ensure conceptual equivalence and acceptability of WSWS in Malay prior to its utilization in research and clinical practice. However, to complete the cultural adaptation process, future psychometric validation is planned to be conducted among Malay speakers.